(untitled) (Journal of actual problems of jurisprudence, 2018)
This article discusses the prevention of crime on the basis of scientific principles, providing timely analysis of the necessary information during the investigation, as well as the practice areas of law enforcement bodies regulated by law. Definitions of criminal information on the detection and investigation of crimes are subject to forensic registrations. Key words: forensic registration, organizational, fingerprinting, filing, identification.